The factor structure and psychometric properties of the Perceived Relationship Quality Component (PRQC) inventory in the Malaysian context - Chua Bee Seok; Siau Ching Sin; Mimi Fitriana; Jasmine Adela Mutang; Hon Kai Yee; Walton Wider; Rosnah Ismail (ASR Research India, 2022)
The Perceived Relationship Quality Component (PRQC) Inventory developed by Fletcher et al. (2000) was used to assess relationship quality. PRQC consists of 18 items to measure the degree of relationship quality among partners. The aims of this study were to determine the factor structure and psychometric properties (i.e., reliability and validity) of PQRC in the Malaysian context. A sample of 560 (246 males, 314 females) Malaysian adults with partners participated in the current study. The respondents were asked to complete the PQRC through an online survey. The exploratory factor analysis extracted two factors labeled “general relationship quality” (15 items) and “passion” (3 items) which accounted for 63.78% of the total variance in the items of a quality relationship. The general relationship quality factor was re-categorized into five sub-components. The label for the five sub-factors was derived from the original scale (i.e., intimacy, commitment, love, satisfaction, and trust). However, the items measuring each factor were based on the load values in the factor and this result was not consistent with the original scale by Fletcher et al. The results revealed a high level of reliability for the total scale of PQRC and its components. The result of concurrent validity also supported that the PQRC was a valid measure of relationship quality, and its utilities in the Malaysian context is proven.